Glycerol Reduces Cross Hybridization on Nitrocellulose Membrane - Narendra Yoga Hendarta; Abu Tholib Aman; Asmarani Kusumawati; Tri Wibawa (Jurnal Sain Veteriner, 2020)
Lateral flow assay (LFD) based nucleic acid lateral flow (NALF)  method has been developed recently. The method met point of care testing (POCT) as simple and rapid procedures, less equipment, and can be performance by less skilled technician. NALF based on nucleic acid hybridizationis  more economical then immunochromatography assay which use antibody-antigen recognition. Cross hybridization has issued while used to differentiate organism with high GC content and high homology as high similarity genome. Some techniques has applied to give high stringency condition avoid cross hybridization reaction but need more procedure to apply. We found glycerol applied to buffer assay could reduce cross hybridization on nitrocellulose membrane. The study used 2 kinds of high stringency buffer as PBS and SSC bases and high concentration of ssDNA amplicon as sample. Without glycerol ingredient gave cross hybridization signal on test line. But used glycerol could reduce those even omitted with PBS based buffer assay. Beside those, glycerol could significantly increased hybridization signal in SSC based buffer assay (p<0.05).